2013
DOI: 10.1002/ajmg.a.35717
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in Mowat–Wilson syndrome: Delineation of the electroclinical phenotype

Abstract: Mowat-Wilson syndrome (MWS) is a genetic disease caused by heterozygous mutations or deletions of the ZEB2 gene and is characterized by distinctive facial features, epilepsy, moderate to severe intellectual disability, corpus callosum abnormalities and other congenital malformations. Epilepsy is considered a main manifestation of the syndrome, with a prevalence of about 70-75%. In order to delineate the electroclinical phenotype of epilepsy in MWS, we investigated epilepsy onset and evolution, including seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 26 publications
(38 reference statements)
4
56
2
1
Order By: Relevance
“…In our group, similarly to the literature, the first seizure occurred at a mean age of 1 year and 8 months, and in three patients, it occurred within the first year of life, in contrast with the observations of Cordelli et al, who rarely observed the start of epilepsy in the first year of life 19 . A fever-triggered seizure, in most cases, is the first seizure and is frequent 19 ; fever-triggered seizure was observed in four patients of our patients, at a median age of 1 year and 2 months. Nonfebrile seizures typically started usually afterwards, with a mean age of onset of 2 years and 10 months (varying from 9 months to 5 years).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In our group, similarly to the literature, the first seizure occurred at a mean age of 1 year and 8 months, and in three patients, it occurred within the first year of life, in contrast with the observations of Cordelli et al, who rarely observed the start of epilepsy in the first year of life 19 . A fever-triggered seizure, in most cases, is the first seizure and is frequent 19 ; fever-triggered seizure was observed in four patients of our patients, at a median age of 1 year and 2 months. Nonfebrile seizures typically started usually afterwards, with a mean age of onset of 2 years and 10 months (varying from 9 months to 5 years).…”
Section: Discussioncontrasting
confidence: 53%
“…Nonfebrile seizures typically started usually afterwards, with a mean age of onset of 2 years and 10 months (varying from 9 months to 5 years). Another seizure characteristic was apparent activation during sleep, also observed in a previous study 19 . All of our patients presented frequent seizures during sleep, and two of them presented with exclusively sleep seizures.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We recently delineated the electroclinical phenotype of epilepsy in MWS. In these patients, epilepsy is usually characterized by frontal lobe and atypical absence seizures, often preceded by fevertriggered seizures; in addition, we observed an age-dependent electroencephalography (EEG) pattern with frequent diffuse frontal dominant spike and wave discharges during the awake state and a near to continuous spike and wave activity during slow sleep (Cordelli et al, 2013).…”
Section: To the Editorsmentioning
confidence: 88%
“…26 One of the major challenges posed by MWS is the recurrence of seizures. 27 In 2013 Cordelli et al 28 hypothesized that a distinct electroclinical phenotype featuring focal and atypical absence seizures (which are often preceded by febrile seizures) and age-dependent electroencephalogram changes can be detected in the majority of patients with MWS.…”
Section: Discussionmentioning
confidence: 99%